Nonsquareness in Musielak-Orlicz-Bochner Function Spaces - Shaoqiang Shang; Yunan Cui; Yongqiang Fu (Abstract and Applied Analysis)
The criteria for nonsquareness in the classical Orlicz function spaces have been given already. However, because of the complication of Musielak-Orlicz-Bochner function spaces, at present the criteria for nonsquareness have not been discussed yet. In the paper, the criteria for nonsquareness of Musielak-Orlicz-Bochner function spaces are given. As a corollary, the criteria for nonsquareness of Musielak-Orlicz function spaces are given.